Distal Metaphyseal Ulnar Shortening Osteotomy: Technique, Pearls, and Outcomes - Khouri, Joseph S. (Thieme Medical Publishers, 2014)
Background Ulnar sided wrist pain is a commonly encountered complaint of the hand surgeon, and ulnar impaction is a common cause. Surgical treatment aims to reduce the force transmitted through the ulna and traditionally includes diaphyseal ulnar shortening osteotomy and the “wafer” procedure. These procedures have known shortcomings. We describe an alternative option known as the distal metaphyseal ulnar shortening osteotomy (DMUSO). Materials and Methods Retrospective review of eight procedures was undertaken to assess radiographic healing, objective measurements of wrist and forearm motion, grip and pinch strength, and subjective measures of Disabilities of the Arm, Shoulder, and Hand (DASH), Patient-Rated Wrist Evaluation (PRWE), and Michigan Hand Outcomes Questionnaire (MHQ) at a minimum of 12 months following surgery. Description of Technique A wedge osteotomy is made in the osteochondral region of the distal metaphysis of the ulna, and a headless compression screw is used for fixation. Results Five women and three men underwent DMUSO with average follow up at 13 months; the dominant wrist was affected in 7 of 8 patients. The affected wrist had less motion in all planes, and grip and pinch strength was also less in the affected wrist, but only wrist extension was significantly different from the contralateral side. These findings likely did not have an effect on the clinical outcome. Subjective outcomes included average DASH score of 13 (0–35), PRWE 19 (40–11), and MHQ score of 88 (85–100). Conclusions DMUSO is a viable option for patients with ulnar impaction syndrome. It requires intra-articular exposure of the distal radioulnar joint (DRUJ) but is less invasive then diaphyseal shortening. It permits early and reliable return of joint motion and function while avoiding the potential need for hardware removal by using a buried screw.